IMPLEMENTASI METODE ANT COLONY OPTIMIZATION (ACO) UNTUK PEMILIHAN JALUR ARTERNATIF TERPENDEK KASUS KEMACETAN LALULINTAS KOTA SEMARANG TIMUR - Teguh Setiadi (UNIVERSITAS STEKOM, 2020)
Abtract The One of the problems that contributed to the worsening traffic conditions, which will be used as research material here is the problem of road narrowing on the road segment that is packed with traffic flow. The road narrowing is a part of the road with the traffic capacity condition subsequently smaller than the up stream. Such road conditions can occur for example when entering the bridge, the occurrence of an accident that causes some of the width of the road is closed, in the event of road improvements or other conditions, causing the change of vehicle travel from the free flow becomes disrupted resulting in decreased speed and increased inter density vehicle. To overcome the problems that exist in the industrial world. Ant Colony Optimization belongs to the Swarm Intelligence group, which is one type of development paradigm used to solve optimization problems where the inspiration used to solve the problem comes from insect swarm behavior or swarms. from this research study are the factors that influence the traffic congestion and the program of action plan that will be done to handle traffic congestion problem in Semarang city road especially in Semarang Timur road Mranggen Semarang. A traffic congestion problem problem with the determination of the shortest pathway using ACO (Ant Colony Optimization).